Public debt in sub-Saharan African countries: determinants and economic effects - Okwoche, Princewill U (School of Economics, 2022)
One of the key macroeconomic policy issues that emerged in the wake of the global financial crisis is the persistent increase in public deficits and debt across the globe. Among researchers and policy makers, this has been the subject of an intense and ongoing debate that mainly seeks to address two issues, namely, the determinants of the growing debt and the economic effects thereof. While most of the debate centres on the advanced and emerging market economies, only a limited number of studies have looked at the case of Sub-Saharan Africa (SSA) countries. This is despite the fact that many countries in the sub-region have been through debt crises in previous decades and are currently facing the imminence of another crisis. This thesis extends the public debt literature by examining the drivers and growth effects of public debt with a focus on SSA countries. The aim is to carry out a more comprehensive analysis of public debt that accounts for the nuances of the sub-region. The thesis is composed of three distinct but interrelated studies. The first study examines the drivers of public debt while the second study focuses on the growth effects of debt. Both studies employ panel econometric techniques using data for SSA countries. The third study is motivated by recent empirical evidence which shows that the drivers and growth effects of public debt do vary substantially across countries due to unique country-specific factors which may not be accounted for in a panel data framework. The study therefore aims to compare country-specific evidence with the evidence obtained from the studies that employ panel data on SSA countries. It focuses on the country case of Nigeria and examines both the determinants and growth effects of public debt. The focus on Nigeria is important due to its position as SSA's most populous and largest economy. Moreover, the country's public debt history is similar to that of most SSA countries. Hence, this study is likely to provide results comparable to studies that utilize panel data for SSA countries. The first study on the determinants of public debt in SSA contributes to the existing literature in two important ways. First, whereas much of the recent discussions around the topic employ descriptive methods, this study employs formal econometric methods namely, the pooled OLS, fixed effects, and the GMM-type methods of Arellano-Bond and Arellano-Bover/BlundellBond. While the fixed effects method helps to deal with unobserved country and time-specific fixed effects, the GMM methods go beyond to account for both the dynamic panel bias and the potential endogeneity in the debt-growth relationship. Overall, the aim of employing a variety of panel estimation techniques is to ensure robustness and facilitate the comparison of the results. Second and more important, instead of focusing only on the macroeconomic factors as previous studies have done, this study also accounts for the influence of armed conflict, governance quality, and regime-type, which are uniquely important to SSA countries. Empirical analyses are aided by data on 40 SSA countries spanning 1996-2017. The findings confirm the role of economic, socio-political and institutional variables in explaining the growth of public debt in SSA. Specifically, the study provides compelling evidence supporting the debt-reducing roles of economic growth and governance quality, and the debt-inducing role of conflict. Regarding the policy relevance of these findings, we note that there have been some uncertainties around the growth prospects of SSA countries in recent years. Additionally, the incidence of violent conflict has recently increased (Barrett, 2018), coupled with the low quality of governance and institutions prevalent in many SSA countries. The findings therefore, have relevant policy implications that can contribute to the efforts towards debt sustainability in SSA countries. The second study examines the growth effects of public debt in SSA using an augmented growth model that includes public debt and its squared term to account for the possible presence of a nonlinear effect. Most studies on the effects of debt on growth, particularly following the global financial crisis, have focused mainly on the advanced and emerging countries. Also, most previous studies have assumed that the debt-growth nexus is homogeneous across groups, and that countries are cross-section dependent. This study addresses these issues while focusing on SSA countries. The focus on SSA provides the opportunity to account for the factors that are unique to the sub-region, namely, the quality of institutions and policies, conflict, and adverse terms of trade shocks. The study employs the fixed effects and system GMM methods under the assumption of homogeneity, and the mean group estimators when assuming that the debt-growth nexus is heterogeneous across countries. It employs a dataset comprising 24 SSA countries spanning 1980-2015. This time period is determined by the data on government gross debt to SSA countries in the Historical Public Debt Database as compiled by Abbas et al. (2011). Mainly, the results strongly affirm the non-linear relationship between public debt and growth, and show that the Debt Laffer curve applies to SSA countries. Furthermore, the results confirm the generally low debt-carrying capacity of SSA countries. A key policy implication of the study is the need for SSA countries to acknowledge their limited capacity to sustain large amounts of debt. Additionally, a comparative analysis of short-term and long-term debt highlights the importance of having a balanced debt structure to aid the management of public debt. The third study examines the determinants of public debt and its non-linear effects on economic growth in Nigeria. It contributes to the existing literature in three distinct ways. First, in addition to the macroeconomic factors underlying the evolution of public debt in Nigeria, the study accounts for the influence of socio-political factors, including armed conflict and governance quality. To the best of the researcher's knowledge, this would be the first study to take this approach to the debate in the literature focusing on Nigeria. Second, whereas previous studies on Nigeria have mainly employed the external debt component, this study employs the total public debt, as well as the individual components, internal and external debt, for a more comprehensive analysis of Nigeria's public debt. Third, it focuses on the non-linear aspect of the debt-growth nexus which has also been largely ignored in the literature on Nigeria. The study relies on annual time series data sourced from the Central Bank of Nigeria and World Development Indicators spanning 1970-2017. Empirical analyses are carried out using the auto-regressive distributed lag (ARDL) approach to cointegration. The analyses of the determinants of public debt produced results largely in line with those obtained from the study on SSA countries. Economic variables tend to have a strong influence across the regressions. In particular, government's fiscal position, oil price, the real interest rate, and the real exchange rate, are consistently significant across the regressions. Although armed conflict is significant in the external debt model, it turns out that socio-political variables do not play a significant role in the model for Nigeria. Turning to the question of the debt-growth nexus, this study presents compelling evidence of a nonlinear relationship between public debt and growth for the case of Nigeria, similar to the evidence obtained from the panel of SSA countries. There is, albeit, a difference in the nature of the nonlinear relationship. Whereas the panel study presents several threshold estimates that do not reflect the debt-carrying capacity of SSA countries, this study presents a threshold estimate of 56% for total public debt, which does not differ much from the IMF's sustainable threshold of 45% for Nigeria and other lower-middle income countries. Based on these findings, it is important for the government to exercise restraint on spending by ensuring that deficits are created mainly for profitable investments that can yield future streams of income.